Feasibility of two high-intensity interval training protocols in cancer survivors - Schlüter, Kathrin; Wiskemann, Joachim; Rosenberger, Friederike; Schneider, Justine (Medicine and science in sports and exercise, 2019)
PurposeHigh-intensity interval training (HIIT) is a time-efficient and promising tool for enhancing physical fitness. However, there is lack of research concerning safety and feasibility of HIIT in cancer survivors. Therefore, two different HIIT protocols were investigated in terms of safety